Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak Badan yang Terdaftar di KPP Pratama Surakarta - Setyo Purwanto, Agung, Dra. Mujiyati,M.Si (2015)
This research was aimed to test the effect of tax-paying awareness, tax rules comprehension, positive view point of tax system effectiveness, and service quality towards the faithfulness of tax-payers, in this case, institution, registered in KPP Pratama of Surakarta. The population of this research was all of the tax-payers, in this case institution, registered in KPP Pratama of Surakarta. The number of samples in this research was 39 respondents taken by certain criteria. This research belonged to quantitative one with questionnaire contained certain criteria employed as the method of data collection. The hypothesis was examined using Multiple Linear Regression analysis, with t test, F test, and coefficient of determination (Adj). The result showed that tax-paying awareness variable and positive view point of tax systemeffectiveness variable has no relation or influence towards the faithfulness of tax-paying. Furthermore, tax rules comprehension variable and service quality variable has a relation or influence towards the faithfulness of tax-paying. It was shown from the result for the value of R2earned in Multiple Regression analysis that the number of coefficient of determination with adjusted R2 was 0.381. It meant that 38.1% of the the faithfulness for tax-paying variable could be explained by the variable of tax-paying awareness, tax rules comprehension, positive view point of tax system effectiveness, and service quality. Meanwhile, the rest, 61.9%, was explained by other external factors which were not a part in this research. Key words: positive view point of tax system effectiveness, service quality, tax-paying awareness, tax rules comprehension, the faithfulness of tax-payers.